배추 종간 잡종의 소포자배양에 의한 Double haploid 집단의 플라보노이드 함량 분석 - 서미숙(Mi-suk Seo); 원소윤(So Youn Won); 강상호(Sang-ho Kang); 김정선(Jung Sun Kim) (Journal of plant biotechnology, 2017)
One of the most important species, Brassica rapa encompasses a variety of commercial vegetables, such as the Chinese cabbage, pak choi and oilseed crops. The LP08 of yellow sarson (Brassica rapa ssp, tricolaris) have a distinct morphology, with yellow seed color and a unique tetralocular ovary. LP21 of pak choi (Brassica rapa ssp, chinensis) have a dark brown seed color and bilocular ovary. In this study, we generated double haploid plants by crossing the LP08 (maternal variety) and LP21 (paternal variety), using microspore culture. A total of 66 accessions with various morphological characteristics were used for content analysis of flavonoids. The three flavonoids, quercetin, naringenin and kaempferol, showed differing contents in the two crossing parents. The Chinese cabbage type 'Chiifu' was used as the control. The highest accumulation of total flavonoids was observed in LP08. The lowest mean total flavonoids were found in 'Chiifu'. Among the 66 DH accessions, the quercetin contents of 18 accessions showed higher content than LP08. Kaempferol content was also high, and was found to be 79.7% of the total flavonoid content. Naringenin content was low at 2.8%, and was not detected in 22 accessions. Interestingly, the quercetin content positively correlated with the kaempferol content. These results can be used to identify genetic locus and genes related to useful traits. Phenotypic analysis of 66 DH accessions can further be used for natural selection of good breeding materials in B. rapa. 본 연구에서는 유지형 배추인 LP08과 청경채형 LP21을 교배한 교잡종 $F_1$을 소포자 배양하여 유전적으로 고정된 계통을 획득하였다. 엽의 결각 유무 및 결각수에서 다양한 형태적 특징을 보이는 66개 고정계통을 대상으로 항암 및 항산화 물질로 알려진 플라보노이드의 함량을 분석하였다. 66개 고정 계통의 엽의 결각 유무와 플라보노이드 함량 간 상관관계는 관찰되지 않았다. 양친으로 사용된 LP08, LP21 그리고 결구 배추형 품종인 Chiifu를 대상으로 플라보노이드 분석을 실시한 결과, quercetin, naringenin, 및 kaempferol 함량의 다양한 분포가 관찰되었다. 또한 모계인 LP08에서 가장 높은 총 플라보노이드 함량을 나타내었고 결구 배추형인 Chiifu에서 가장 낮은 함량을 보였다. 66개 고정 계통을 대상으로 플라보노이드 함량을 분석한 결과, quercetin은 LP08 보다 높은 함량을 보이는 18 계통이 확인되었으나 naringenin과 kaempferol에서는 교배친 보다 높은 함량을 보이는 계통을 발견할 수 없었다. 총 플라보노이드 함량에서 kampferol은 79.7 %, quercetin은 17.4 %의 비율을 보였고 naringenin의 경우 2.8 %로 거의 대부분의 계통에서 가장 낮은 함량을 보이고 22개 계통에서는 전혀 발견되지 않았다. 또한 성분간 상관관계를 분석한 결과 quercetin과 kaempferol의 함량간에 유의한 상관관계가 있음을 확인할 수 있었다. 본 실험의 결과는 향후 플라보노이드 생합성 기작 관련 유전자 탐색을 위한 자료로 활용할 예정이다. 또한 고정 계통을 대상으로 다양하고 광범위한 형질 조사를 실시하여 배추의 품종 개발이 가능할 것으로 기대된다.